The Industrialisation of Soviet Russia 2: Soviet Collective Farm, 1929-1930 - Davies, R. W. author. aut Link
X, 216 p.
Keywords: During the events described in The Socialist Offensive the collective farms achieved a commanding position in the Soviet countryside. They were planned as giant, fully socialist enterprises, modelled on the state-owned factories, and employing wage labour. By the summer of 1930 the collective-farm compromise had been introduced. Collective farmers were permitted to retain a personal household plot and their own animals; and a free market continued side by side with state planning. This system continued throughout the Stalin period important features of it remain in the Soviet Union today. The emergence of the collective farm in 1929-30, discussed in detail in the present volume, was thus a crucial stage in the formation of the Soviet system.